Mutagenicity of Edible Palm Oil on the Ghanaian Market before and after Repeated Heating. Issue 12 (31st October 2013) - Asare, George A.; Okyere, Genevieve O.; Asante, Matilda; Brown, Charles A.; Santa, Sheila; Asiedu, Bernice
Abstract: Red palm oil produced in Ghana largely by village folks has never been tested for its mutagenic potential. The study aimed at determining the mutagenicity of high‐energy heated red palm oil (RRPO) and refined, bleached imported palm oil (PO) on the Ghanaian market. Samples of RRPO and PO were 1× and 5× heated for 10 min at 180 °C with a cooling period of 5 h in‐between. Unheated, together with heated samples, were tested for mutagenicity using Salmonella typhimurium TA 98 and TA 100 tester stains. Unheated PO was negative for the Ames mutagenicity test with TA 98 strain. However, 1× and 5× heated PO were mutagenic ( P = 0.05, each). Testing PO, using TA 100 strain was negative. RRPO was mutagenic with TA 98 strain for heated oils ( P = 0.05, each). Assays with TA 100 strain showed highly significant mutations ( P = 0.001, each) that increased with increasing heating frequency. PO 1× and 5× heated samples caused significant frameshift mutation in the S. typhimurium TA 98 strain. RRPO caused highly significant point and frameshift mutations in heated samples. Furthermore, unheated RRPO mutagenic potential has serious health implications.